JAJAO (Revitalisasi Kepemimpinan Lokal Masyarakat Kampung Gamta Distrik Misool Barat Kepulauan Raja Ampat) - Muhamad Yusuf (Jurnal EL-RIYASAH, 2020)
The Gamta basin located in West Misool district has some unique aspects of its culture, where the culture of the community is influenced by the coming immigrants, thus forming a new culture that has been preserved by the people. Since the reign of the Tidore sultanate, the kings' rights were conferred on the Lilinta and Gamta territories only to control and conquer their territories, dividing Misool by some powers under King Lilinta, Jajao Gamta, Jajao Waigama and Captain Fafanlap. Currently, the public's understanding of Jajao is very low, not only for those outside the Gamta community, but also for the Gamta people in the area. Even in today's generation, where Jajao's leadership is not so visible. Research Outcome: The Tidore Sultanate has influenced the dissemination of cultural or complex features of the Tidore community to the West Misool community, introducing a new nature in the traditional leadership of the West Misool community. The duties and functions of the Gamta indigenous community are based on customary ceremonies, or issues of tenure and the application of customary laws that reflect social class and its role in indigenous society.